Analisis #JagaASN Sebagai Media Kampanye di Indonesia pada Pemilihan Kepala Daerah Tahun 2020 - Muhammad Eko Atmojo; Awang Darumurti; Vindhi Putri Pratiwi (PERSPEKTIF, 2022)
The purpose of this article is to see how effective the campaign model carried out by the State Civil Apparatus Commission is, especially with the #JagaASN jargon. The government through the State Civil Apparatus Commission has launched a bureaucratic neutrality campaign through social media. This is done considering the implementation of regional head elections during the COVID-19 pandemic. In addition, this campaign also hopes to reduce the number of ASN neutrality cases in Indonesia. So, with this campaign, it is hoped that the government can provide quality services and realize regional head elections with integrity. This study uses qualitative research methods, using several research tools. The research tools used are Nvivo and VOSviewer. Based on the results of the study, the case of ASN neutrality in Indonesia, especially in the 2020 regional head election, is still quite high. Where this can be seen based on data from the State Civil Apparatus Commission that violations in the 2020 regional head elections are quite high with several cases as many as 864 ASN reported, while for 635 ASN violating and receiving KASN recommendations to be followed up, for ASN who have sanctioned by the staffing officer of 500 ASN. In addition, based on the processed results of NVivo 12+, it was also found that 82% of ASN were declared to be in the category of bureaucratic/ASN neutrality violations. The details are that 18% of ASN became a candidate pair's success team, 9% used state facilities, 31% participated in activities and sided with one of the candidates, and the last 21% ASN participated in the candidate pair's campaign.